Nucleophilic Addition to Nitrones Using a Flow Microreactor - Arakawa, Yukihiro; Ueta, Shun; Okamoto, Takuma; Minagawa, Keiji; Imada, Yasushi (Synlett, 2020)
Nucleophilic addition reactions of soft carbon nucleophiles to nitrones in a flow microreactor are reported for the first time. Under microflow conditions at 30 to 0 °C, a range of nitrones can be efficiently transformed into the corresponding oxyiminium ions by reaction with either acyl halides or trialkylsilyl triflates. These can subsequently undergo the addition of nucleophiles including allyltributylstannane, ketene methyl tert-butyldimethylsilyl acetal, and N-silyl ketene imines to afford the corresponding adducts in high yields; such reactions at a similar temperature under batch conditions resulted in lower yields because of undesired side reactions.
Keywords: nitrones; flow; microreactor; nucleophilic addition; nitrogen-containing compounds